Firn density and compaction rates 50km upstream of South Pole - Koutnik, Michelle; Waddington, Edwin D.; Lilien, David; Conway, Howard; Fudge, T. J.; Stevens, Christopher Max (IEDA: US Antarctic Program Data Center, 2023)
This dataset comprises firn density and compaction rate measurements from USP50, a site 50km upstream of South Pole. (89.54 S, 137.04 E). Firn compaction rates were measured for two years (from January 2017 to December 2018) using string potentiometers to measure borehole shortening. Density measurements include field measurements from December 2016 and January 2017 as well as measurements made at the National Science Foundation Ice Core Facility (NSF-ICF) on a core that was returned to the U.S. for analysis. The dataset also includes measurements of (near-surface) temperature inside the boxes that housed the potentiometers. The raw data are voltage measurements from a datalogger. The dataset includes these raw data as well as processed data. It also includes the python script used to process the data and relevant files containing site and instrument specifications needed to process the data.